2021
DOI: 10.1093/plphys/kiab312
|View full text |Cite
|
Sign up to set email alerts
|

Membrane nanodomains and transport functions in plant

Abstract: Far from a homogenous environment, biological membranes are highly structured with lipids and proteins segregating in domains of different sizes and dwell times. In addition, membrane are highly dynamics especially in response to environmental stimuli. Understanding the impact of the nanoscale organization of membranes on cellular functions is an outstanding question. Plant channels and transporters are tightly regulated to ensure proper cell nutrition and signaling. Increasing evidence indicates that channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 158 publications
1
19
0
Order By: Relevance
“…CWLP and PRP940 display clustered co-localization in the PM with aquaporin PIP2;1 in nanodomains (103). Our study confirms that C-terminal 8CM domains of both proteins are preprint (which was not certified by peer review) is the author/funder.…”
Section: Cw-pm Linker Functions Of Cwlp and Prp940supporting
confidence: 75%
See 4 more Smart Citations
“…CWLP and PRP940 display clustered co-localization in the PM with aquaporin PIP2;1 in nanodomains (103). Our study confirms that C-terminal 8CM domains of both proteins are preprint (which was not certified by peer review) is the author/funder.…”
Section: Cw-pm Linker Functions Of Cwlp and Prp940supporting
confidence: 75%
“…6E). These results indicated that CWLP and PRP940 form aquaporin complexes independently of FLOT2 in distinct nanodomains and thus revealed a novel class of PM-ND complexes (25,103,127).…”
Section: Aquaporin Binding and Recruitment Of Pp2a Phosphatase B''-su...mentioning
confidence: 83%
See 3 more Smart Citations